175k views
1 vote
Help me please

f(x) = ln(x { } ^(2) + 2 )


User Dalilah
by
5.2k points

1 Answer

2 votes
➡Answer: x=√(e^y-2)

❇Explanation:
Step1: Let f(x)=y,then

↪y=ln(x²+2)

Step2: Converting it into exponential form,

↪e^y=x²+2

↪x²=e^y-2

Step3: Taking square root of both sides,

↪x=√(e^y-2)

❇Note:

ln means log with base e.

So in step 2 , base e of ln (x²+2) goes to other side in the form e^y. That is simply the property of log I used there..

Hope this helps!
User Shirland
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.